Impact of tip-vortex modeling uncertainty on helicopter rotor blade-vortex interaction noise prediction - Vouros, Stavros; Goulos, Ioannis; Scullion, Calum; Nalianda, Devaiah; Pachidis, Vassilios (Vertical Flight Society, 2020)
Free-wake models are routinely used in aeroacoustic analysis of helicopter rotors; however, their semi-empiricism is accompanied with uncertainty related to the modeling of physical wake parameters. In some cases, analysts have to resort to empirical adaption of these parameters based on previous experimental evidence. This paper investigates the impact of inherent uncertainty in wake aerodynamic modeling on the robustness of helicopter rotor aeroacoustic analysis. A free-wake aeroelastic rotor model is employed to predict high-resolution unsteady airloads, including blade-vortex interactions. A rotor aeroacoustics model, based on integral solutions of the Ffowcs Williams-Hawkings equation, is utilized to calculate aerodynamic noise in the time-domain. The individual analytical models are incorporated into an uncertainty analysis numerical procedure, implemented through non-intrusive Polynomial Chaos expansion. The potential sources of uncertainty in wake tip-vortex core growth modeling are identified and their impact on noise predictions is systematically quantified. When experimental data to adjust the tip-vortex core model are not available the uncertainty in acoustic pressure and noise impact at observers dominated by blade-vortex interaction noise can reach up to 25% and 3.50 dB respectively. A set of generalized uncertainty maps is derived, for use as modeling guidelines for aeroacoustic analysis in the absence of the robust evidence necessary for calibration of semi-empirical vortex core models.
Keywords: Blade-vortex interaction noise; Uncertainty quantification; Helicopter noise prediction; Free-wake aerodynamics